Vztahy mezi výskytem protilátek proti Toxoplasma gondii a klinickými nálezy vysetrených kocek - Svoboda, M; Svobodová, V; Konrád, J (Veterinarni medicina, 1988)
Within a three-year period, 178 clinically healthy and 442 sick cats (patients of the Clinic for Small Animal Diseases of the University of Veterinary Medicine, Brno) were examined for the presence of antibodies to Toxoplasma gondii. Antibodies to T. gondii were detected in 34.8% of the animals without clinical signs of the disease and in 54.3% of the sick cats (P less than 0.01). Compared with the group of clinically healthy cats, the specific antibodies occurred significantly more frequently in the cats suffering from diseases of the digestive tract (P less than 0.01), particularly in those with acute gastroenteritis, and in those having liver disorders (P less than 0.01; P less than 0.05). A statistically significantly higher occurrence of antibodies to T. gondii was also recorded in the cats with disorders of the nervous system (P less than 0.05; P less than 0.01), particularly in those with symptoms of extraordinary aggressivity at the age span from four months to three years. Enlarged lymph nodes were found out in 44% of the cats having antibodies to T. gondii. This is 15% more than the average for the investigated set of animals, which is a statistically significant dependence (P less than 0.01).
Keywords: Toxoplasmosis, Animal; Cat Diseases; Cats; zvířata; nemoci koček; toxoplazmóza zvířat; Toxoplasma; Antibodies, Protozoan; protilátky protozoální; kočky; Animals